Public-private partnership between Satbayev university and SK Geoservice LLP: Enhancing collaboration in technological innovation and production - Ratov Boranbay; Kosminov Arthur; Kuttybayev Aidar; Tabylganov Maksat; Seksenbay Mukhamejan (E3S Web of Conferences, 2024)
The article provides a detailed examination of public-private partnerships between Satbayev University and drilling tool manufacturer SK Geoservice LLP. It begins by discussing the underlying reasons for this collaboration, such as the demand for innovation and the advancement of drilling tool production. Subsequently, the article analyzes the partners’ interactions and their respective roles in enhancing the design and production processes of drilling tool manufacturing. Successful instances of the university’s research groups’ scientific endeavors being implemented by drilling tool manufacturing experts from the private sector are cited, indicating a high level of cooperation and mutual benefit. The article concludes by highlighting the partnership’s positive impact on the drilling tools market’s development, private entrepreneurship support and growth in the region, and the training of highly skilled personnel. It suggests that these outcomes create new opportunities for further cooperation and growth. Overall, the article underscores the significance of public-private partnerships in advancing science and technology and advocates for their continued deepening and expansion in Kazakhstan. It also notes that such partnerships contribute to enhancing the quality of education in drilling-related fields and bolstering the competitiveness of Kazakhstani companies in the global market.